ANALISIS PENGARUH DIMENSI SERVQUAL TERHADAP LOYALITAS PELANGGAN BED COVER AND FRIENDS KEDIRI - Yuswanto, Meidy Nur; Meiliana, Restin; Sasongko, M. Zuhdi (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of SERVQUAL dimension comparising reliability, assurance, tangibles, emphaty, and responsiveness on customer loyalty at Bed Cover and Friends, a convection business in Kediri. The research employs a quantitative approach through a questionnaire distributed to 100 respondents. The data were analyzed using multiple linear resgression and tests for validity and reliability. The result indicate that significant impact on customer loyalty. Tangible and emphaty also show positive influence, although to a lesser extent, while responsiveness has a negative but insignificant effect. The novelty of this research lies in its focus on a rarely studied local business and its emphasis on the importance of reliability and assurance in fostering customer loyalty in the local bedding industry.